A meta-analysis of the efficacy of programmed cell death 1/its ligand inhibitors plus cytotoxic T-lymphocyte-associated antigen 4 inhibitors in non-small cell lung cancer - Lin, Li; Xiao, Lu; Li, Lei; Chen, Chen; Zhang, Haorong; Yu, Changyan; Zhang, Lanfang; Wei, Anhua; Li, Wei (Frontiers in Pharmacology, 2024)
Background: Immune checkpoint inhibitors (ICIs), either as monotherapy or in combination with chemotherapy, have improved the therapeutic outcome for non-small cell lung cancer (NSCLC). However, the efficacy of combination therapies, such as programmed cell death 1(PD-1)/its ligand (PD-L1) and cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4) inhibitors, in targeting different pathways remains unclear. We performed a meta-analysis to determine whether the addition of a CTLA-4 inhibitor to PD-1/PD-L1 therapy improves the efficacy of PD-1/PD-L1 monotherapy in NSCLC. Methods: We systematically searched various electronic databases for suitable trials. Only randomized controlled trials (RCTs) comparing the clinical efficacy of PD-1/PD-L1 with and without CTLA-4 were included in the analyses. The meta-analysis software RevMan 5.3 was used for statistical analyses. Results: A total of seven RCTs were retrieved. The results suggested that the combination of CTLA-4 and PD-1/PDL-1 inhibitors did not show enhanced efficacy over PD1/PDL-1 inhibitor monotherapy as determined by overall survival (OS) (HR = 0.98, 95% CI = 0.84–1.14, p = 0.79), progression-free survival (PFS) (HR = 0.92, 95% CI = 0.81–1.06, p = 0.25), and objective response rate (ORR) (HR = 1.08, 95% CI = 0.96–1.21, p = 0.19). Furthermore, the combination immunotherapy was associated increased toxicity as evidenced by increased incidence of any type adverse events (AEs) (RR = 1.06, 95% CI = 1.00–1.13, p = 0.03), grade ≥3 immune-mediated AEs (RR = 1.58, 95% CI = 1.36–1.82, p < 0.05), and treatment discontinuation (RR = 1.83, 95% CI = 1.46–2.28, p < 0.05). Conclusion: Combining anti-CTLA-4 with anti-PD-1/PD-L1 therapy did not improve the therapeutic efficacy, and was associated with greater toxicity than anti-PD-1/PD-L1 monotherapy in patients with advanced NSCLC. Further investigation of the combination immunotherapy in specific subsets of patients is warranted to identify and define the patient-specific benefits of this combination. Systematic Review Registration:https://www.crd.york.ac.uk/prospero/, identifier CRD42023435399